Transformation thermomechanics of R-phase in TiNi shape memory alloys - Tanaka, K.; Nishimura, F.; Kato, H.; Miyazaki, S. (Archives of Mechanics, 1997)
Thermomechanical behaviour in TiNi shape memory alloys after the R-phase transformation is formulated from the continuum mechanical point of view based on two metallurgical processes progressing simultaneously: the lattice distortion in the R-phase and the variants reorientation of the twinned R-phase variants. The start and evolution of both processes are assumed to be governed by conditions similar to the yield condition and the associated consistency condition in plasticity. The evolution equations are derived by solving a conditional extremum problem derived from the dissipation inequality. Uniaxial behaviour is discussed under several thermomechanical load conditions. The simulation of the recovery stress induced during constraint heating presents a clear coupled effect of the two metallurgical processes.